Photography, landscape and modern architecture: Januário Godinho, Teófilo Rego and Álvaro Cardoso de Azevedo – The HICA conection - MOREIRA, César Machado (2013)
In the first half of the 20th century in Portugal, as the result of a policy based on agriculture and on a way of life in which access to more than a bare minimum of goods was denied, the Portuguese Estado Novo, presided over by António de Oliveira Salazar (1889-1970), maintained, until the 1940s, an indefinite stance in relation to industrialization which was reflected in weak management of the nation's hydrological resources and in the late creation of large hydroelectric power stations. It was only in 1945, with the end of World War II, that favourable conditions were created for economic development founded on a basis of industrialization. At that time, due to their importance in bringing electrical power to the country and its consequent industrialization, hydroelectric plants for the production and distribution of electrical power began to be strongly encouraged by the Estado Novo. A meeting between technology and architecture, these large projects introduced significant alterations to the territory of Portugal, bringing substantial modifications to the existing landscape. At locations that were far from the main centres of population, large building projects would be constructed, utilizing an architecture in which integration into the landscape and technology constituted environmental, historical and cultural values of immense interest. The understanding of the importance of propaganda and of the crucial role of image in publicizing the large building projects that were undertaken can be clearly seen in the activities promoted by the Estado Novo. In publications and at major events, photographers and their work came to be a constant presence in public life, recording scenes that appeared to the Portuguese public to be illustrating moments of great national importance. It is these photographs, much more so than the texts of the time, that can reach out to us today and allow us to go back to the past. Photography transports us from real, chronological time to a time of memory that is fixed in the image, replacing the real people and events that have long disappeared, the understanding of which helps us to reconstruct history. The aim of this essay is precisely that of analysing the potential of photography as a tool for the development of new interpretations of the theory, criticism and history of modern architecture, with particular focus on a specific moment at the beginning of the second half of the 20th century during which several hydroelectric plants were built in the north of Portugal, interventions which led to the construction of a variety of new landscapes on national territory.